IMPROVING THE VOCABULARY ACHIEVEMENT OF THE SECOND YEAR STUDENTS BY USING FAIRY TALES - Magfirah Nurdin; Muhammad Asfah Rahman; Ahmad Talib (JTechLP: Journal of Technology in Language Pedagogy, 2022)
This research is aimed at discovering whether or not the use of fairy tales improves the vocabulary achievement of students in their second year of MTsN 2 Kota Makassar. This study used a quasi-experimental approach with one group working as the control group, and the other as the experimental group. A 25-item vocabulary test was employed as the research instrument. The populations of this research were 40 students from the VIII.B and VIII.C classes in the academic year 2020-2021. This class was taken as the sample randomly through the cluster random sampling technique from 11 classes. To collect data, the pre-test and the post-test procedures were used. This study's findings reveal that the college students’ vocabulary mastery after receiving the treatment made positive progress. The average of the student's performance from the pre-test to the post-test can be demonstrated. The vocabulary achievement of the class which is taught by using fairy tales showed improvement (64.19 to 87.62). The computation and examination of the t value revealed that it was less than level significant (0.000<0.05). Thus, it concludes that the use of fairy tales improves the students’ vocabulary achievement of the second-year students MTsN 2 Kota Makassar.